Would Islamic Finance Have Prevented The Current Global Financial Crisis? - O M Alhejaili, Mohammad (The journal of contemporary issues in business and government, 2022)
The embodiment of Islamic banking is so not the same as traditional banking, as it employments a risk-sharing procedure that provides a genuine opportunity to consider whether or not the way in which ordinary banking is attempted still remains the finest alternative, in all cases couple this with the fact that there has been increased globalisation of financial services, in recent years, and the opportunity to use Islamic financing principles in a wide range of countries is now much more relevant. Concerns have been raised about the activities of the conventional banking sector, particularly following the recent financial crisis. Accordingly, taking a gander at choices, for example, the Islamic financial area is a genuine chance to roll out appropriate improvements. Despite this, there are challenges confronting the Islamic banks in attempting to acquire general allure. One of the major issues is the fact that many Islamic banking establishments are dealing with developing countries which have their own set of challenges, especially in times of economic difficulties. Besides, the legitimate structures encompassing Islamic keeping money have not kept pace; As a result, many of the Islamic banking rules and regulations are outdated and will no longer help the core of how Islamic banks operate. With this in mind, it is proposed that a much stronger legal structure is needed to promote Islamic banking, and that, in the long run, Islamic banks are unlikely to gain widespread global acceptance. It takes time to persuade investors all over the world to change their ways, and trust must be earned. Nonetheless,, without having a legal structure in place, it is difficult to gain this level of confidence; therefore, getting the frameworks in place will be a crucial part of ensuring that the Islamic banking sector is in the appropriate place to benefit from a period of growth which is likely to take place as part of the recovery from the current economic position.